Cognition of the mothers of patients with Duchenne muscular dystrophy. Issue 6 (21st September 2020) - Demirci, Hasan; Durmus, Hacer; Toksoy, Guven; Uslu, Atilla; Parman, Yesim; Hanagasi, Hasmet
Abstract: Duchenne muscular dystrophy (DMD) has been found to be associated with cognitive impairment. However, few studies have addressed cognitive impairment among mothers of children with DMD. In the present study, the neuropsychological profiles of both carrier mothers (C‐Ms) and noncarrier mothers (NC‐Ms) were examined, and the findings were compared with healthy control mothers (HC‐Ms). There were 90 participants, consisting of 31 C‐Ms, 24 NC‐Ms, and 35 HC‐Ms, each of whom completed a neuropsychological test battery. C‐Ms had poorer cognition performance in attention, working memory, immediate verbal memory, visuospatial skills, and executive functions than NC‐Ms, and HC‐Ms. This study provides evidence that there may be cognitive impairment in mothers of patients with DMD. The cognitive impairment of C‐Ms has similarities to that seen in children with DMD.